2022
DOI: 10.3389/fcimb.2022.849662
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Analysis of Togaviridae in Mosquito Viromes Isolated From Yunnan Province in China Reveals Genes from Chikungunya and Ross River Viruses

Abstract: We collected 5,500 mosquitoes belonging to six species in three locations in China. Their viromes were tested using metagenomic sequencing and bioinformatic analysis. The affluent viral sequences that were detected and annotated belong to 22 viral taxonomic families. Then, PCR was performed to confirm the results, followed by phylogenetic analysis. Herein, part of mosquito virome was identified, including chikungunya virus (CHIKV), Getah virus (GETV), and Ross river virus (RRV). After metagenomic analysis, sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The results also suggest that HMV2 strains from different geographical ranges may have originated from a common ancestor or may have genetically recombined in the same way. In addition, it had been suggested that some viruses infect hosts over wide geographic areas, possibly being introduced via being wind-blown, cyclonic action, or flying animals ( 13 ), and that HMV2 may have spread widely across different regions in this manner. Eventually, the exact mechanism of recombination evolution and the virus type of HMV2 could not be determined from these existing data, and in-depth studies need to be conducted to determine the origin and class of this virus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results also suggest that HMV2 strains from different geographical ranges may have originated from a common ancestor or may have genetically recombined in the same way. In addition, it had been suggested that some viruses infect hosts over wide geographic areas, possibly being introduced via being wind-blown, cyclonic action, or flying animals ( 13 ), and that HMV2 may have spread widely across different regions in this manner. Eventually, the exact mechanism of recombination evolution and the virus type of HMV2 could not be determined from these existing data, and in-depth studies need to be conducted to determine the origin and class of this virus.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the development of metagenomic sequencing technology has promoted the detection and monitoring of mosquito viruses, thereby resulting in the discovery and research of a large number of new mosquito viruses, including Getah virus ( 12 ), Ross River virus ( 13 ), Banna orbivirus ( 14 ), and many others. This provided new insights into the complexity and diversity of the viruses that are carried by mosquitoes, and these had important implications for the dynamic surveillance of pathogens and the responses to emerging and reemerging infectious diseases ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Reagents together with methods used in RNA extraction and metaviral sequencing have been expounded in our previous study ( Feng et al, 2022 ). Moreover, the DNA barcodes employed in metaviral sequencing are displayed in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…The West African phylogeny is deep-rooted in West Africa, with approximate inferred root in the 1960s, coinciding with the first recorded spillover from enzootic cycles 2 . Recently isolated detection in China has been described before 16 . In order to understand viral emergence and transmission dynamics of this novel clade in Senegal, we employed a Bayesian phylogenetic reconstruction approach.…”
Section: Main Textmentioning
confidence: 99%